Poly(3‐hydroxybutyrate) fuels the tricarboxylic acid cycle and de novo lipid biosynthesis during Bacillus anthracis sporulation. Issue 5 (30th March 2017) - Sadykov, Marat R.; Ahn, Jong‐Sam; Widhelm, Todd J.; Eckrich, Valerie M.; Endres, Jennifer L.; Driks, Adam; Rutkowski, Gregory E.; Wingerd, Kevin L.; Bayles, Kenneth W.
Summary: Numerous bacteria accumulate poly(3‐hydroxybutyrate) (PHB) as an intracellular reservoir of carbon and energy in response to imbalanced nutritional conditions. In Bacillus spp., where PHB biosynthesis precedes the formation of the dormant cell type called the spore (sporulation), the direct link between PHB accumulation and efficiency of sporulation was observed in multiple studies. Although the idea of PHB as an intracellular carbon and energy source fueling sporulation was proposed several decades ago, the mechanisms underlying PHB contribution to sporulation have not been defined. Here, we demonstrate that PHB deficiency impairs Bacillus anthracis sporulation through diminishing the energy status of the cells and by reducing carbon flux into the tricarboxylic acid (TCA) cycle and de novo lipid biosynthesis. Consequently, this metabolic imbalance decreased biosynthesis of the critical components required for spore integrity and resistance, such as dipicolinic acid (DPA) and the spore's inner membrane. Supplementation of the PHB deficient mutant with exogenous fatty acids overcame these sporulation defects, highlighting the importance of the TCA cycle and lipid biosynthesis during sporulation. Combined, the results of this work reveal the molecular mechanisms of PHB contribution to B. anthracis sporulation and provide valuable insight into the metabolic requirements for this developmental process in Bacillus species. Abstract : Poly( R )‐3‐hydroxybutyric acid (PHB) is the most abundant storage compound of carbon and energy in bacteria. Here, we demonstrate that PHB mobilization furnishes the TCA cycle and de novo lipid biosynthesis during Bacillus anthracis sporulation which are required for biosynthesis of spore components critical for spore integrity and resistance. Combined, our results clarify the role of PHB utilization during sporulation and provide valuable insight into the metabolic requirements for this developmental process in Bacillus species.